Antibiotic Susceptibility of β-Glucuronidase-Positive Escherichia coli Isolated from Poultry Products in Morocco - Oumaima Fazza; Mireille Favard Ennachachibi; Houda Ennassiri; Abdelaziz Hmyene (International Journal of Food Science)
Poultry products are one of the main foodstuffs consumed in Morocco. The deterioration of their hygienic quality and the emergence of antibiotic resistance are the major public health problems. This study was carried out to determine the level of emergence of antibiotic resistance. For that, between May 2021 and June 2022, poultry products (e.g., minced meat, sausage, and meat) were collected aseptically in sterile bags from retail stores in different cities of Morocco, labeled, and transported in chilled conditions to the laboratory. The bacterial analysis was performed within 24 hours. Isolation and identification of Escherichia coli were performed according to the Moroccan standard NM ISO 16649 2018. Antimicrobial susceptibility determination of 23 antibiotics was tested using the Kirby-Bauer disk diffusion method. The results showed a high level of antimicrobial resistance to amoxicillin (58%), amoxicillin-clavulanic acid (54%), piperacillin (63%), trimethoprim (32%), nalidixic acid (46%), and ofloxacin (43%). 58 isolates (60%) were positive for beta-lactamase class A (penicillinase) test detection, and 2 isolates (3%) produced extended-spectrum beta-lactamases. The high level of resistance demonstrated in this study should alert health organizations in the country. An establishment of surveillance programs to control the use and the administration of antibiotics in the poultry field and initiation of reliable methods to follow up on the latest updates on the emergence of bacterial resistance is a necessity.